Free radical processes in rat liver in experimental diabetes, malignant growth and their combination - I. A. Goroshinskaya; E. M. Frantsiyants; I. V. Kaplieva; L. A. Nemashkalova; L. K. Trepitaki; P. S. Kachesova; E. I. Surikova; V. A. Bandovkina; M. I. Morozova; I. M. Kotieva (Исследования и практика в медицине)
Purpose of the study. To study the intensity of lipid peroxidation (LPO) and indicators of antioxidant protection in the liver of rats of different sexes with combined pathology – the growth of Guerin's carcinoma in presence of experimental type 1 diabetes mellitus.Materials and methods. The levels of malondialdehyde (MDA) and diene conjugates (DC), the activities of superoxide dismutase (SOD) and catalase, and the levels of vitamins A and D were studied by conventional spectrophotometric methods in liver tissue samples from males and females with alloxan‑induced diabetes mellitus (DM), transplanted Guerin’s carcinoma (GC) and in animals with combined pathologies (GC growth in presence of diabetes mellitus), as well as in intact rats.Results. The levels of both LPO markers in intact females were significantly higher than in males: MDA by 3 times, DC by 2 times. The development of DM led to an increase in the content of MDA and DC in the liver of males compared with intact animals, which indicated an intensification of LPO. At the same time, there was an almost twofold increase in SOD activity, a decrease in catalase activity, and an increase in the ratio of enzymes by 2.8 times. In females, there was no increase in LPO in the liver; there was only a less pronounced increase in SOD activity than in males. At the same time, SOD activity in males was 37 % higher than in females, and catalase activity, on the contrary, was lower by 33 %, which caused a twofold excess of the ratio of enzymes in males relative to females. Among animals with GC, only males had an increase in SOD by 2.5 times, a decrease in catalase activity, and an increase in the SOD/Catalase ratio by 3 times relative to intact animals, which may be due to pronounced sex differences the SOD activity and SOD/Catalase ratio in males were 3–4 times higher than that of females. The levels of MDA and DC in males with GC growing in presence of DM remained elevated, although to a somewhat lesser extent than in DM alone, while in females both indicators were reduced. The ratio of vitamins E and A increased only in males. SOD activity and SOD/Catalase coefficient in animals of both sexes with combined pathologies were significantly lower than in groups with only DM or GC.Conclusions. The data showed that diabetes mellitus changes the specificity of oncogenesis depending on the sex of the animals. Males with the growth of Guerin's carcinoma in presence of diabetes in conditions of inhibition of SOD activity and a decrease in the ratio of conjugated enzymes of the first line of antioxidant defense demonstrate an intensification of LPO accompanied by an increase in the non‑enzymatic unit of the antioxidant system, while there is no increase in LPO in females, and the indicators of antioxidant activity change to a lesser extent.